A relação entre inovação e produtividade nas empresas hoteleiras - uma perspectiva de análise utilizando a análise envoltória de dados (DEA) e a modelagem de equações estruturais (SEM) - Oliveira, Jaime de Souza (2018)
Critics of the Resource-Based View (RBV) consider that the analyzes supported in the performance of the operational capabilities are, in general, very aggregated, which harms the examination that intends to adequately understand the composition and interaction of the operational resources used. In addition, management research recognizes the importance of capabilities to achieve competitive advantage, but these studies rarely investigate capabilities at the operational level where they actually occur. These gaps guide the development of the investigation in this research that, from a more operational perspective, seeks to understand how companies organize their structures to induce innovations and create competitive advantages that translate into superior operational performance. Thus, based on Economics, with the support of the theoretical model related to the Frontier of Production Possibilities, which establishes limits for the productive capacity of a company, the efficiency of each one of the sample companies was measured, with the support of the DEA methodology (Data Envelopment Analysis). On the other hand, Evolutionary Economics and Dynamic Capabilities, both theories that position routines as the foundation of capabilities, support the orientation of this research in studying capabilities through their underlying routines. Therefore, capabilities were modeled as a second-order latent construct, and each set of routines was measured, supported by CFA-SEM (Confirmatory Factor Analysis and Structural Equation Modeling), as a latent first-order construct from measurement items developed according to the theory. In addition, this way of conceptualizing and measuring capabilities, from a set or bundle of routines, is supported by requirements such as inimitability, value and rarity that are characteristics of the capabilities, in correspondence with the RBV. Therefore, this research proposes a dual analysis standard oriented to the operational aspects of the company that, on the one hand, investigates, compares and thoroughly evaluates the efficiency in the use of resources and in obtaining results, and on the other hand, it maps, analyzes and measures operational procedures or routines. In order to make feasible the proposed analysis, we used primary data from 212 Brazilian hotels (response rate 43%), randomly selected, in 2016. The results confirm empirical evidence that capabilities emerge from a number of interrelated routines and that there is a strong conceptual link between resources, routines, and performance, broadening the understanding of the specific ways in which capabilities can be built and developed. In addition, this research provides knowledge to guide Brazilian hotel managers in their decisions on innovation management, in order to make their organizations more efficient and competitive.